Mass Spectrometry Imaging for Glycome in the Brain - Hasan, Md. Mahmudul; Mimi, Mst. Afsana; Mamun, Md. Al; Islam, Ariful; Waliullah, A. S. M.; Nabi, Md. Mahamodun; Tamannaa, Zinat; Kahyo, Tomoaki; Setou, Mitsutoshi (Frontiers in Neuroanatomy, 2021)
Glycans are diverse structured biomolecules that play crucial roles in various biological processes. Glycosylation, an enzymatic system through which various glycans are bound to proteins and lipids, is the most common and functionally crucial post-translational modification process. It is known to be associated with brain development, signal transduction, molecular trafficking, neurodegenerative disorders, psychopathologies, and brain cancers. Glycans in glycoproteins and glycolipids expressed in brain cells are involved in neuronal development, biological processes, and central nervous system maintenance. The composition and expression of glycans are known to change during those physiological processes. Therefore, imaging of glycans and the glycoconjugates in the brain regions has become a "hot" topic nowadays. Imaging techniques using lectins, antibodies, and chemical reporters are traditionally used for glycan detection. Those techniques offer limited glycome detection. Mass spectrometry imaging (MSI) is an evolving field that combines mass spectrometry with histology allowing spatial and label-free visualization of molecules in the brain. In the last decades, several studies have employed MSI for glycome imaging in brain tissues. The current state of MSI uses on-tissue enzymatic digestion or chemical reaction to facilitate successful glycome imaging. Here, we reviewed the available literature that applied MSI techniques for glycome visualization and characterization in the brain. We also described the general methodologies for glycome MSI and discussed its potential use in the three-dimensional MSI in the brain.